Anatomy Practice during COVID-19 Pandemic - Arif Wicaksono (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Anatomy learning required practice to understanding and comprehend. Anatomical practice used aids such as cadaver. Cadaver was a corpse preserved for anatomy learning. Practice using cadavers was a way of studying the human body with very real details and experiences and must be done offline. The Coronavirus Disease 2019 (COVID-19) pandemic had limited lives, learning, and practice due to the risk of transmission. The interest in understanding some material offline must be facilitated with a supportive environment by medical institutions.Objective: This study will provide recommendation in implementing safe anatomy practice during COVID-19 pandemic.Methods: This article used literature review of anatomical practice and health protocols from books, journals, and guides from home and abroadResults: offline anatomy practice using cadaver should be implemented to help student understand human body more specific and more detail.Conclusion: Health protocol should and can be implemented in offline anatomy practice during COVID-19 pandemic. Anatomy practice can be performed during pandemic using strict health protocols.